2022
DOI: 10.3390/electronics11111690
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a User Interface Based on Multimodal Interaction to Control a Robotic Arm for EOD Applications

Abstract: A global human–robot interface that meets the needs of Technical Explosive Ordnance Disposal Specialists (TEDAX) for the manipulation of a robotic arm is of utmost importance to make the task of handling explosives safer, more intuitive and also provide high usability and efficiency. This paper aims to evaluate the performance of a multimodal system for a robotic arm that is based on Natural User Interface (NUI) and Graphical User Interface (GUI). The mentioned interfaces are compared to determine the best con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…• The mental workload and the usability of the proposed system should also be taken into consideration. Goyzueta in [2] has oriented the use of a Kalman Filter based processing to have an optimal estimation of the hand position of the operator to control the robotic arm by LM due to the characteristics of the LM sensor and the noises it has, the Kalman filter is optimal to obtain more accurate information of the hand position. However, although a correct hand estimation is obtained, physiological tremors caused by the musculoskeletal composition of the operator are still present.…”
Section: Our Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…• The mental workload and the usability of the proposed system should also be taken into consideration. Goyzueta in [2] has oriented the use of a Kalman Filter based processing to have an optimal estimation of the hand position of the operator to control the robotic arm by LM due to the characteristics of the LM sensor and the noises it has, the Kalman filter is optimal to obtain more accurate information of the hand position. However, although a correct hand estimation is obtained, physiological tremors caused by the musculoskeletal composition of the operator are still present.…”
Section: Our Approachmentioning
confidence: 99%
“…System 1 is composed of a Kalman Filter. In [2] is used this filter to control a robotic arm using leap motion oriented to EOD applications, performing an in-depth analysis of the performance of this interface compared to traditional controls such as keyboards or keypads. Korayem in [16] uses the Kalman filter to eliminate noise in the input of his system for a surgical application, and in [17] it studies in depth the physiological tremors of the operators using the LM sensor to measure them and the fast Fourier transform to determine their spectral range, concluding that physiological tremors constitute a significant contributor to end-effector vibrational motions, while Kalman filter extensions are used to minimize overall system noise.…”
Section: Our Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In [16], they use a haptic interface for robotic control in which immersive interaction with the person being rescued significantly improves task performance compared to other control systems; and visual feedback further increases user performance metrics. In [17], they evaluate different multimodal interfaces to find the system with the most intuitive and least operator workload; using visual interfaces, GUI interfaces and NUI interfaces. It is shown that a multimodal interface helps considerably in an intuitive teleoperation improving robotic efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…An application is the tracking of objects, where it is necessary to estimate the distance of the object, thus achieving a high accuracy in real time [26]. Being complementary to other systems such as "leap motion" for interfaces "man-robot" for applications in robots EOD (bomb disposal) [27].…”
Section: Introductionmentioning
confidence: 99%